Special exercises with ropes, rubber bullets and their impact in some biomechanical variables in the 100m hurdles ran for juniors - Ali Sadiq Dhiab; Saeed, Sarmad; Hameed, Intisar Rashid (International Journal of Psychosocial Rehabilitation, 2020)
The rubber ropes exercises affected muscle groups, which in turn affects the corners of the conditions of the body before and over the barrier where affected the time passed To change the angle of the approaching and payment impact on passing each times the barrier 1-5 That passed over the barrier 1and gate 5 impacts on the nature of the achievement, where time has become less Find the values of cruise missiles and other phases and stages of pitch angle other categories which it enshrines stood as compelling rejection men’s 110m hurdles Find the value of the instant messaging distances between different barriers and stages Studies by adding rubber sling barriers race categories, measurement of kinematic variables Emphasis on the development of the force by means of various tools and resistances added to during the designated as performance similar to affect the physical abilities of biomechanical variables for each of the normal step outdistancing jogging former stages